THE EFFECT OF USING WATTPAD APPLICATION IN IMPROVING READING COMPREHENSION OF THE TENTH GRADE AT SMA NEGERI 9 MAKASSAR - Rizal, Nurul Amalia; Anugrawati, Nunung; Burhanuddin, Wildhan (Journal of Computer Interaction in Education, 2023)
This research aimed to find out whether the effect of using Wattpad in Improving students’ Reading Comprehension or not at Tenth Grade Students of SMA Negeri 9 Makassar. This research used quantitative research with a pre-experimental approach. The researcher gave pre-test to students, and then the researcher gave the students’ treatment using Wattpad Application. After treatment is given, researcher gives the students’ post-test. The population in this study were students of the class X SMA Negeri 9 Makassar. The sample of this research was the students of the class X.7, included 29 students. The sample was taken by Purposive Sampling. The result showed that the t-test value was higher than the t-table value. The t-test value of reading comprehension in terms of Literal Comprehension was higher than the t-table (14.75>2.04841), and the t-test value in terms of Interpretative comprehension was higher than the t-table (15.17>2.04841). The t-test of the indicators in the students' Reading Comprehension skills t-test produced a result that was higher than the t-table (29.92>2.04841). It was concluded that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. It means that using the Wattpad application was effective to improve students’ reading comprehension.